Expert Interviews at the Global Launch of National Policies and Strategies for Food, Land, and Water Systems Transformation (NPS) - International Livestock Research Institute (International Livestock Research Institute, 2022)
On 17 May 2022, ILRI Nairobi hosted the Kenya launch and inception meeting of National Policies and Strategies for Food, Land, and Water Systems Transformation (NPS), a new One CGIAR initiative working in six countries. Featuring a high-level panel of guests from a diverse range of Kenyan national and county-level institutions, as well as the global director for systems transformation and director general of the International Food Policy Research Institute (IFPRI) Johan Swinnen and director general of the International Livestock Research Institute (ILRI) Jimmy Smith, participants discussed key policy issues, including responding to current crises ranging from drought and rising food, fertilizer and energy prices to tackling livelihood insecurity and poverty.